Controllable molecular aggregation and fluorescence properties of 1, 3, 4-oxadiazole derivatives. Issue 44 (20th October 2015) - Wang, Haitao; Chen, Fangyi; Jia, Xiaoshi; Liu, Huimin; Ran, Xia; Ravva, Mahesh Kumar; Bai, Fu-Quan; Qu, Songnan; Li, Min; Zhang, Hong-Xing; Brédas, Jean-Luc
Abstract : In H-aggregation, BOXD-6 adopts a linear conformation and forms a one-dimensional layered structure; in J-aggregation, it adopts a Z-shaped conformation and forms a more ordered two-dimensional layered structure. Abstract : The molecular self-assembly behaviour of 2, 2′-bis-(4-hexyloxyphenyl)-bi-1, 3, 4-oxadiazole (BOXD-6) in solution, on surfaces and in bulk crystals, and its photo-physical properties were studied via a combination of experimental techniques and theoretical calculations. It is found that BOXD-6 molecules self-assemble into both H- and J-aggregates at moderate concentration (∼10 −4 M) and then transit to exclusive J-aggregates at higher concentration (∼10 −3 M) in tetrahydrofuran. In H-aggregation (α polymorph), BOXD-6 adopts a linear conformation and forms a one-dimensional layered structure; in J-aggregation (β polymorph), it adopts a Z-shaped conformation and forms a more ordered two-dimensional layered structure. A π-stacking structure is observed in both cases, and adjacent molecules in J-aggregation show larger displacement along the molecular long axis direction than that in H-aggregation. Although J-aggregates are almost the only component in concentrated solutions (10 −3 M), both H- and J-aggregates can be obtained if concentrated solution is transformed onto substrates through a simple drop-casting method. Such a phase transition during film formation can be easily avoided by adding water as a precipitator; a film with pure J-aggregates is then obtained. In order to get more information on molecular self-assembly, intermolecular interaction potential energy surfaces (PES) were evaluated via theoretical calculations at the DFT level (M062x/6-31G**). The PES not only confirm the molecular stacking structures found in crystals but also predict some other likely structures, which will be the target of future experiments.